The Influence of Emotional and Spiritual Intelligence on Students' Honest Behavior - Muhammad Isa Anshari; Muhammad Samsul Hady; Esa Nur Wahyuni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Education is an effort to change an individual's mindset and behavior to mature a person through learning activities aimed at exploring and developing a person's abilities, both intellectually, emotionally, socially, and spiritually. One of the goals of national education is to build character. Honesty is one of the crucial and important aspects of character education. This study aims to determine the influence of emotional and spiritual quotient on students' honest behavior. This research was conducted at MTs Wahid Hasyim 01 Dau in the odd semester of the 2024/2025 academic year. This research uses a quantitative method with a correlational approach. The data collection method in this study uses a questionnaire. The results of this study show: 1). The majority of students' emotional quotient is at the moderate category level, with 71 students or 39.7% having an average score of 75.55. 2). Most of the students' spiritual quotient is at a moderate level, with 69 students or 38.5% having an average score of 75.41. Most of the students' honest behavior falls into the moderate category, with 71 students or 39.7% having an average score of 77.51. 4). There is a simultaneous influence of emotional and spiritual intelligence on honest behavior based on an F-value of 106.213, which is greater than the F-table value of 3.05 with a significance value of 0.000, which is less than 0.05.